Interaksi Simbolik Perempuan Sandwich Generation dengan Orang Tua, Anak, dan Suami (Studi di Nagari Pauah, Kecamatan Lubuk Sikaping, Kabupaten Pasaman) - Ovelga Wandy Putri; Mira Elfina; Fachrina (LPPM STISIP IMAM BONJOL, 2026)
Studies on sandwich generation women generally focus on economic and psychosocial aspects. However, a more fundamental yet often overlooked issue is how women interpret and negotiate their roles within social structures that construct idealized expectations of the “good woman”. In Minangkabau culture, women are often assumed to hold strong positions within the family. Yet in practice, patriarchal dominance persists, placing women in a contradictory position between symbolic glorification and burdensome social realities. This study aims to explore the meanings constructed by sandwich generation women to their parents, children, and husband, as well as their roles as daughter, mother, and wife. Using Herbert Blumer’s symbolic interactionism theory and a qualitative approach, the research was conducted in Nagari Pauah, Lubuk Sikaping Subdistrict, Pasaman Regency involving six purposively selected informants through in-depth interviews. Findings reveal that women perceive parents as resilient figures and moral obligations; children as social investments and reasons for marital endurance; and husbands as “third children”, protectors, confidants, and social status markers. Their roles are interpreted as that of a father’s substitute, family fate changer, reflection of mother’s struggle, moral guardian, and multitasking human. These findings highlight the need to recognize women’s subjective meanings and call for structural and cultural changes to support more equitable gender relations in the family.